Depletion of B‐Cells With Rituximab Improves Endothelial Function and Reduces Inflammation Among Individuals With Rheumatoid Arthritis. Issue 5 (21st October 2014) - Hsue, Priscilla Y.; Scherzer, Rebecca; Grunfeld, Carl; Imboden, John; Wu, Yuaner; del Puerto, Gus; Nitta, Elaine; Shigenaga, Judy; Schnell Heringer, Amanda; Ganz, Peter; Graf, Jonathan
Abstract : Background: Individuals with rheumatoid arthritis (RA) are at increased risk for cardiovascular disease, partly due to systemic inflammation and endothelial dysfunction. B‐cells play an important pathogenic role in the inflammatory process that drives RA disease activity. Rituximab, a chimeric murine/human monoclonal antibody that depletes B‐cells, is an effective therapy for RA. The purpose of this study was to determine whether B‐cell depletion with rituximab reduces systemic inflammation and improves macrovascular (brachial artery flow‐mediated dilation, FMD) and microvascular (reactive hyperemia) endothelial function in RA patients. Methods and Results: RA patients received a single course of rituximab (1000 mg IV infusion at baseline and on day 15). FMD, reactive hyperemia, inflammatory markers, and clinical assessments were performed at baseline, week 12, and week 24. Twenty patients (95% female, median age 54 years) completed the study. Following treatment, FMD improved from a baseline of 4.5±0.4% to 6.4±0.6% at 12 weeks (mean±SE; P <0.0001), followed by a decline at week 24; a similar pattern was observed for hyperemic velocity. Significant decreases in RA disease scores, high‐sensitivity C‐reactive protein, erythrocyte sedimentation rate, and circulating CD19+ B‐cells were sustained through week 24. Cholesterol and triglycerides became significantly although modestly elevated during the study. Conclusions: Depletion of B‐cells with rituximab improved macrovascular and microvascular endothelial function and reduced systemic inflammation, despite modest elevation in lipids. Given these results, rituximab should be evaluated in the future for its possible role in reducing excess cardiovascular risk in RA. Clinical Trial Registration: URLhttp://ClinicalTrials.gov . Unique identifier: NCT00844714.